Modern and Innovative Approaches to the Organization of Students’ Self-Education in Higher Educational Institutions - Zakhro Umarova (Newinera Publisher, 2020)
Self-education is gaining momentum. Today, the main challenge for universities is to launch open online courses that anyone can access. Such an initiative is a signal to educational organizations that they must rebuild their educational process. It is necessary not only to broadcast information, but also to engage in tutoring support of students, immerse them in real projects and tasks. This article highlights new viewpoints of methodology of organization of students' self - education in higher educational institution.